1992
DOI: 10.1182/blood.v79.3.765.765
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of globin gene expression in human K562 cells by recombinant activin A

Abstract: Recent studies indicate that a purified protein, activin A, belongs to the transforming growth factor beta (TGF-beta) superfamily. Similar to TGF-beta, activin A can have different biologic activities, depending on the target tissues. We used recombinant activin A to demonstrate a possible regulatory role of this protein in modulating human erythroid differentiation in the human erythroid cell line, K562. Using genomic probes containing the second exon of alpha, beta, gamma, and epsilon globins, relative abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…1A). These results are consistent with a previous report using Northern blot analysis [Frigon et al, 1992]. To examine the contribution of p38 MAPK and ERK, K562 cells were incubated in the presence or absence of p38 MAPK inhibitor (SB203580) or MEK/ERK inhibitor (PD98059) alone, or in combination with activin A for 3 days.…”
Section: Resultssupporting
confidence: 91%
“…1A). These results are consistent with a previous report using Northern blot analysis [Frigon et al, 1992]. To examine the contribution of p38 MAPK and ERK, K562 cells were incubated in the presence or absence of p38 MAPK inhibitor (SB203580) or MEK/ERK inhibitor (PD98059) alone, or in combination with activin A for 3 days.…”
Section: Resultssupporting
confidence: 91%
“…By contrast, in agreement with present findings, many studies had demonstrated that activin A can directly induce erythroleukemia cells into differentiation [Yu et al, 1987[Yu et al, , 1989Eto et al, 1987;Broxmeyer et al, 1988]. Incubation of purified erythroid progenitors and K562 cells with activin A was also found to lead to an increase in globin transcripts and hemoglobin accumulation [Frigon et al, 1992;Shao et al, 1992a]. Therefore, in addition to the indirect actions for promoting the proliferation of erythroid precursor cells, activin A may directly affect erythroid differentiation via interaction with receptors in the erythroid cells [Shao et al, 1992a;Yu et al, 1991].…”
Section: Discussionsupporting
confidence: 91%
“…4 Many studies have demonstrated that activin A can potentiate the proliferation and differentiation of erythroid progenitors in vitro [5][6][7][8] and induce human K562 to become haemoglobin-containing cells. 5,9 In addition, many in vivo studies in rats and mice [10][11][12] support the hypothesis that this protein may have erythropoietic enhancing activities. 5 It is conceivable that activin A molecules may also play a role(s) in the inflammatory response because inflammatory mediators, such as TNF-a, IL-1, interferon-g (IFN-g) and lipopolysaccharide (LPS), which are involved in host defence, also markedly enhance the production of activin A.…”
mentioning
confidence: 93%